2023
DOI: 10.1111/ijfs.16364
|View full text |Cite
|
Sign up to set email alerts
|

Effects of pomelo peel sponge layer insoluble dietary fibre addition on the properties of the dough and bread

Abstract: In this study, the influences of different proportions (0%, 5%, 10%, 15% and 20% w/w) of pomelo peel sponge layer insoluble dietary fibre (PP-IDF) on the technological quality, structural character and sensory evaluation of wheat dough and bread were studied. Results showed that the addition of PP-IDF improved the viscoelasticity of dough and reduced its enthalpy of freezing-thawing. Meanwhile, PP-IDF significantly improved the quality of bread during storage. Compared with the control, the 7-day moisture rate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 57 publications
0
2
0
Order By: Relevance
“…The specific volume of GF bread was evaluated with the rapeseed displacement method, using changes to the weight and volume of the bread. The baking loss represents the loss of moisture from the bread during baking and was measured according to a previous study [ 15 ]. Equation (1) was used to determine baking loss.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The specific volume of GF bread was evaluated with the rapeseed displacement method, using changes to the weight and volume of the bread. The baking loss represents the loss of moisture from the bread during baking and was measured according to a previous study [ 15 ]. Equation (1) was used to determine baking loss.…”
Section: Methodsmentioning
confidence: 99%
“…The addition of various dietary fibres can have a significant impact on the texture, colour, moisture content, shelf life, and nutritional properties of GF bread [ 13 ]. Studies have shown that incorporating corn fibre, barley fibre, and rice bran into GF bread results in a more intense coloration, which is considered a desirable attribute for starch-based GF products [ 14 , 15 ]. Furthermore, the inclusion of dietary fibre effectively reduces bread staling, leading to a significant extension in its shelf life [ 16 , 17 ].…”
Section: Introductionmentioning
confidence: 99%